Rancang bangun sistem balon tampondengan sensor tekanan - Eko Arianto (JHeS (Journal of Health Studies), 2018)
Postpartum Hemorrhage (PPH) contributes to high number of maternal mortality rate (AKI) in Indonesia. The cause of PPH is varied, but the most common case is atonia uteri. There are some medical procedures to prevent PPH, one of which is using a balloon tamponade.Balloon tamponade is a balloon that is used to help stop PPH.This research was carried out by making new balloon tamponade system. The test results shows that the models which have been developed can be used as a better ballon tamponade system.Condoms can be filled up to 1500 ml volume.